PEMBIMBINGAN TEKNIS DAN IMPLEMENTASI SERTIFIKASI HALAL BAGI UMKM UNTUK MENINGKATKAN PEMAHAMAN DAN PENERAPAN STANDAR HALAL: Studi pada Anggota Asosiasi Pengusaha Makanan dan Minuman Indonesia (ASPAMI) Bandung - Zakiah, Kiki; Ratnasari, Anne; Chotijah, Nurul; Suwarsi, Sri; Umar, Tia Muthiah; Ahmadi, Dadi; Male, Adam Truedy (LP2M Universitas Ibrahimy, 2025)
The development of the halal industry globally, including in Indonesia, shows a significant trend. It is driven by growing public awareness of the importance of using sharia-compliant products. The role of Usaha Mikro, Kecil, dan Menengah (UMKM) is crucial in supporting and expanding the development of this sector, as their existence is a major driver of economic growth, although they still face various obstacles, particularly related to the understanding and implementation of halal certification. This Community Service (PKM) is designed to strengthen UMKM knowledge and skills in managing halal-based businesses through training and technical assistance. Activities carried out included outreach, training, Focus Group Discussions (FGDs), technical guidance, and monitoring of 30 food and beverage MSMEs who are members of the Asosiasi Pengusaha Makanan dan Minuman Indonesia (ASPAMI). The activity results showed a significant increase in the understanding and implementation of halal certification, as evidenced by the Wilcoxon test between pretest and posttest scores. Furthermore, implementing this program has significantly contributed to strengthening the position of UMKM, enabling them to survive and compete locally and in increasingly fierce global competition. This program provides education on mapping the halal raw material supply chain and Halal marketing strategies. The sustainability of this program is expected to encourage more UMKM to adopt halal principles and strengthen the national halal ecosystem.